Consumers' body image expressions: Reflection of a Snow White or an Evil Queen - Wagner, Ralf; Singh, Swati (Frontiers in Psychology, 2023)
Introduction The aim of this paper is to explore how minimal-self impacts the body image, projecting it as a reflection of one's approach toward their health and mental well-being. Methods The study takes qualitative data from two countries India and Germany and draws on a qualitative study of 20 individuals who are involved in some kind of physical activity for a long time. This paper examines the body image perspectives from Grimms Brothers fairytale characters showcasing fit and healthy perspectives on Snow White side and projected and superfluous perspectives on Evil Queen side. The study also provides a model deciphering the rationale for both the reflections. Results The body image projection from Snow White perspectives (success & dedication, self-esteem, bodybuilding, and cosmetic surgery) relates to positive reflection of oneself with focus on fitness, discipline, and mental rejuvenation in life. Notably, Evil Queen perspectives (unrealistic makeover, dark side of social media, gain an edge over others, and mental benchmarking with fair skin) reveal these facets as motivators to equip their body as means of physical non-verbal communication assets. Conclusion Analysis shows that there is no clear white or black view of health and fitness projection via body image but it's a gray line that gives wholesome fitness either a holistic mental peace or a competitive or success-oriented approach.